Die ontwerp van ŉ Afrikaanse taakgebaseerde rekenaaronderrigprogram vir internasionale studente aan die Universiteit Stellenbosch - Beukes, Vernita; Adendorff, Elbie (Stellenbosch Papers in Linguistics Plus, 2015)
OpsommingDie navorsing waaroor in hierdie artikel verslag gelewer word, is spesifiek gerig op nie-Afrikaanssprekende internasionale studente aan die Universiteit Stellenbosch (US). Die doel van die breë navorsing wat onderneem word en waarvan in dié artikel slegs gedeeltelik verslag gelewer word, is om die moontlike ontwerp van ŉ taakgebaseerde rekenaarprogram vir die kursus Beginner Afrikaans Vlak 1 te illustreer. Die navorsing val binne twee breë vakgebiede, waarvan die eerste een die taakgebaseerde benadering tot leer en onderrig is en die tweede een rekenaargesteunde taalonderrig (RGTO). Taakgebaseerde leer en onderrig is ŉ onderrigbenadering waar die fokus van die studente op die bereiking van ŉ doelwit geplaas word. Volgens Duran en Ramaut (2006) en Van Avermaet en Gysen (2006) is die vertrekpunt van enige taakgebaseerde benadering ’n behoefte-analise. Vir hierdie studie het die studente ŉ vraelys voltooi. As deel van die behoefte-analise gebruik die studente, saam met die vraelys, die Europese Referensiekader (ERK) (2001) om hulle taalvaardighede te assesseer. Die studente verskaf ook inligting oor onderwerpe wat hulle graag in die klas behandel wil hê. Nadat die taakgebaseerde benadering bespreek is, word daar op Mayer (2009, 2011) se kognitiewe teorie van multimedia-leer gefokus. Dit dien as vertrekpunt vir die tweede vakgebied, naamlik rekenaargesteunde taalonderrig (RGTO) wat verder in hierdie artikel bespreek word. Hierdie teorie verskaf die agtergrond vir enige aktiwiteit wat op die rekenaar ontwerp word. Nadat die kognitiewe teorie van multimedia-leer bespreek is, word daar op vier multimedia-instruksiebeginsels, deur Mayer (2009, 2011) ontwikkel, gefokus, naamlik die oortolligheidseffek, die samehangeffek, die ruimtelike-aangrensingseffek en die verpersoonlikingseffek. Hierdie beginsels word kortliks bespreek, voordat ŉ verbinding tussen die twee vakgebiede gemaak word deur die bevindinge wat sover van studente verkry is, te gebruik en dan prakties te toon hoe een van die instruksiebeginsels moontlik aan die studente voorgestel kan word in die rekenaarprogam.The design of an Afrikaans task-based computer program for international students at Stellenbosch University Extended abstractThe focus of the research discussed in this article is on non-Afrikaans-speaking international students who are served by the Language Centre at Stellenbosch University. The aim of the broad research of which only a part is reported on in this article, is to describe the steps taken in the design of a task-based computer program for the course Beginner Afrikaans Level 1. The Postgraduate and International Office (PGIO) at Stellenbosch University offers several courses for international students. Students have to choose a minimum of five courses in order to transfer the required amount of credits back to their home universities. The Language Centre has close ties with the Postgraduate and International Office because of the language acquisition courses which they present to international students. Foreign students who wish to become proficient in Afrikaans during their stay in South Africa choose to enrol for Beginner Afrikaans Level 1. One of the objectives of this course is that students acquire the Afrikaans being used in social contexts on and around campus. The course focuses primarily on communicative and discourse competencies. Students follow the course for one semester and have class for four hours per week for fourteen weeks. Being a credit-bearing course, students obtain twelve South African university credits for it. The students who follow this course are mainly from America and Europe and more detail on their backgrounds is given in the article. These students mentioned in formal feedback sessions that they would like to have a computer component as part of the course and this request forms the basis for the study. The research bridges two broad disciplines: the task-based approach to teaching and learning (TBLT) and computer assisted language learning (CALL). Task-based teaching and learning is an educational approach where the focus is on achieving a goal; where language becomes the tool and using the language a necessity. According to Duran and Ramaut (2006) and Van Avermaet and Gysen (2006) the starting point of any task-based approach is a needs analysis in order to identify student needs. In this study a needs analysis was conducted specifically to determine why students enrol for this course. In addition the students provided information on topics they would like to cover in class and completed a questionnaire. Besides the completion of a needs analysis and questionnaire, the students used the Common European Framework of Reference (CEFR) (2001) to assess their language proficiency. This framework is familiar to students from European universities (especially students who study languages) as it is the system that is used at their home universities to determine language proficiency. Several European universities base their language syllabi on the CEFR since it provides a basis whereby students can both assess themselves and be assessed by staff at tertiary institutions.After the discussion on the task-based approach, the focus of the article shifts to Mayer’s (2009, 2011) cognitive theory of multimedia learning. This serves as the departure point for the second discipline on which this study is based, namely computer assisted language learning (CALL). This theory provides the background for any activity designed for the computer. Mayer (2009) clearly states that no computer program should be supplied to learners without being designed according to a sound and empirically tested theory. The cognitive theory of multimedia learning provides this basis. Following the description of the cognitive theory of multimedia learning, the emphasis in the article moves to the four design principles, developed by Mayer (2009, 2011). These are: the redundancy principle (people learn better from graphics and narration than from graphics, narration and printed text), the coherence principle (people learn better when unnecessary materials are excluded rather than included), the spatial contiguity principle (people learn better when corresponding words and pictures are placed close to each other) and the personalization principle (people learn better when the words in a multimedia presentation are more conversational and not in a formal style). The researchers then attempt to show how these two disciplines can be correlated. This is done by providing the results obtained from the completed questionnaires, as well as how one of these principles might be presented to students by means of a computer program.